High Concentration Phenol Removal Using Freshwater Microalgae - Al-Zuhair, Sulaiman; Nabil, Mustafa; Abdi, Yusuf; Sayyed, Murad Al; Taher, Hanifa (International Journal of Biotechnology for Wellness Industries, 2016)
The ability of three freshwater microalgae strains, namely Chlorella sp., Pseudochlorococcum sp. and Chlamydomonas sp. to grow in water containing different concentrations of phenol has been tested. The effectiveness of the selected strains to utilize the phenol as a carbon source and reduce its concentration has also been assessed. The phenol removal efficiency and cells growth rates were evaluated at different initial phenol concentrations, in the range of 100-450 ppm. It was found that growing, under a reduced illumination condition, increased the inhibition onset concentration, enhanced the phenol removal and allowed the strains to tolerate higher phenol concentrations reaching 450 ppm. In the tested range of the phenol concentrations, Chlamydomonas sp. has shown to have the highest specific growth rate of 0.59 day-1, whereas Pseudochlorococcum sp showed the highest phenol removal rate of 166 ppm day-1. Three kinetics models that incorporate substrate inhibition were tested to describe the growth, which show almost identical fittings.